Sub-ontologies and ontology views: a theoretical perspective. (25th January 2008) - Rajugan, R.; Chang, Elizabeth; Dillon, Tharam S.
The success of the Semantic Web (SW) relies heavily on formulation and interoperability of well-defined ontologies and their utilisation. Thus, in this context, it is interesting to investigate concepts like ontology view specification, construction and extraction. Here, in this paper, we address one such issue: ontology views. The proposed ontology view mechanism is a Layered View Model (LVM) and is specified and defined using conceptual and logical level semantics, as opposed to a query language. Our aim here is to provide a detailed theoretical foundation for LVM for ontologies. Also, our proposed concepts are illustrated using an industrial case-study example.